Decoupled jaws promote trophic diversity in cichlid fishes. (1st May 2020) - Burress, Edward D.; Martinez, Christopher M.; Wainwright, Peter C.
Abstract: Functional decoupling of oral and pharyngeal jaws is widely considered to have expanded the ecological repertoire of cichlid fishes. But, the degree to which the evolution of these jaw systems is decoupled and whether decoupling has impacted trophic diversification remains unknown. Focusing on the large Neotropical radiation of cichlids, we ask whether oral and pharyngeal jaw evolution is correlated and how their evolutionary rates respond to feeding ecology. In support of decoupling, we find relaxed evolutionary integration between the two jaw systems, resulting in novel trait combinations that potentially facilitate feeding mode diversification. These outcomes are made possible by escaping the mechanical trade‐off between force transmission and mobility, which characterizes a single jaw system that functions in isolation. In spite of the structural independence of the two jaw systems, results using a Bayesian, state‐dependent, relaxed‐clock model of multivariate Brownian motion indicate strongly aligned evolutionary responses to feeding ecology. So, although decoupling of prey capture and processing functions released constraints on jaw evolution and promoted trophic diversity in cichlids, the natural diversity of consumed prey has also induced a moderate degree of evolutionary integration between the jaw systems, reminiscent of the original mechanical trade‐off between force and mobility.